Phosphoglucomutase 1: complete human and rabbit mRNA sequences and direct mapping of this highly polymorphic marker on human chromosome 1. - Whitehouse, D B (1992)
A cDNA clone encoding the mRNA for the highly polymorphic human enzyme phosphoglucomutase 1 (PGM1; EC 5.4.2.2) has been isolated and characterized. This was achieved indirectly by first isolating a rabbit cDNA from an expression library using anti-rabbit PGM antibodies. A comparison of the nucleotide sequences shows that the homologies between human and rabbit PGM1 mRNAs are 92% and 97% for the coding nucleotide sequence and the amino acid sequence, respectively. The derived rabbit amino acid sequence is in complete agreement with the published protein sequence for rabbit muscle PGM. A physical localization of the human PGM1 gene to chromosome 1p31 has been determined by in situ hybridization. Analysis of DNA from a wide variety of vertebrates indicates a high level of PGM1 sequence conservation during evolution.